Sensitivitas rapid test untuk mendeteksi hepatitis surface antigen (HBsAg) pada penderita hepatitis-B - Suwarso, Suwarso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A new rapid-test, sandwich immunochromatography assay technique has been recently introduced for the routine, rapid, qualitative detection of the presence hepatitis-B surface antigen (HBsAgl. To evaluate the sensitivity of rapid test, we studied 39 sera positive and one sera negative for HBsAg with conventional ELISA method. The study found that the minimal detectable level of HBsAg with rapid test was 4.03 ng/ml (range 3,25-4,03 ng/ml), it was 8 times less sensitive than conventional ELISA method (4,03 vs 0,47 ng/m1)Ã¢â¬Â¢ Many factors such as "eddy diffusion" and structure of HBsAg, humidity, direct contact with sunlight and sera of borderline-low level of HBsAg with conventional ELISA had a potency for lower sensitivity of rapid test; conversely, technical factors such as adhesion, migration and viscosity of the samples do not.Key words : rapid test - dry chemistry hepatitis surface antigen (HBsAg) - sensitivity - ELISA.